Hyperuricemia and Cardiovascular Disease: Mechanisms, Associations, and Therapeutic Implications – A Literature Review - Borowski, Maciej; Szczepański, Michał; Dzieszko, Natalia; Kalinowska, Weronika; Kulasza, Paulina Sara; Szeliga, Aleksandra; Książek, Tomasz Karol; Kozłowska, Kinga; Dembicki, Piotr Mikołaj; Francuziak, Anna Ewelina (Quality in Sport, 2025)
Uric acid has emerged as a potential biomarker for cardiovascular risk. Hyperuricemia, described as an abnormally elevated concentration of uric acid in the bloodstream, has been associated with the development of cardiovascular diseases such as hypertension, atrial fibrillation, heart failure, and coronary heart disease. Recent studies have investigated the potential benefits of using uric acid-lowering therapy in slowing the progression of these diseases. In this review, we summarize current evidence on the impact of hyperuricemia on cardiovascular diseases and the effectiveness of urate-lowering therapy in affected patients.